Health related quality of life in individuals at high risk for familial hypercholesterolemia undergoing genetic cascade screening in Brazil. (October 2018) - Souto, Ana Cristina; Miname, Marcio H.; Fukushima, Julia; Jannes, Cinthia E.; Krieger, Jose E.; Hagger, Martin; Pereira, Alexandre C.; Santos, Raul D.
Abstract: Background and aims: Familial hypercholesterolemia (FH) is a genetic disorder associated with high risk of early major cardiovascular events (MACE) that can impact the health related quality of life (HRQoL), however, this association is unclear. This study evaluated HRQoL in index cases (IC) and first-degree relatives (FDR) of individuals at high risk of FH undergoing genetic cascade screening. Methods: Data collection was performed before awareness of molecular diagnosis results. Individuals were divided into four groups according to the molecular diagnosis: IC with (IC+) and without (IC-) identified mutations (n = 93 and n = 175, respectively), and affected (FDR+, n = 231) and non-affected (FDR-, n = 159) FDR of IC+. HRQoL measurements, mental (MCS) and physical component (PCS) scores were carried out with SF-12 questionnaire. Associations were tested by generalized linear models. Results: The mean age was 49 ± 15 years, 42.2% were men, MACE had occurred in 30.7%. Overall, both PCS and MCS did not differ between FH and non-FH individuals, however, IC trended to have lower PCS independent of FH presence ( p =0.003). Lower PCS were associated with female sex ( p =0.018), lower education ( p <0.001), professional inactivity ( p =0.028), previous MACE occurrence ( p <0.001), hypertension ( p =0.016), depression ( p <0.001) and obesity ( p <0.001). Lower MCS were associated with female sex ( p =0.009), previous MACE occurrence ( p =0.034), depression ( p <0.001) and smoking ( p =0.009). Neither the presence of FH causing mutations nor pharmacological lipid lowering treatment was associated with HRQoL. Conclusions: HRQoL is not reduced in both IC and FDR FH individuals in comparison with their non-affected counterparts. Previous MACE and co-morbidities are associated with reduced HRQoL. Highlights: Impact of familial hypercholesterolemia (FH) on health related quality of life (HRQoL) is uncertain Previous cardiovascular disease, and co-morbidities influenced HRQoL negatively Lipid lowering therapy was not associated with HRQoL A FH causing mutation was not associated with HRQoL FH was not associated with HRQoL